Нестационарные взаимодействия ударных и детонационных волн в газах - Баженова Т. В. Татьяна Валерьевна; Гвоздева Л. Г.; Лагутов Ю. П.; Ляхов В. Н.; Фаресов Ю. М.; Фокеев В. П.; Коробейников В. П. Виктор Павлович (Москва, Наука, 1986)
Авт. указаны на обороте тит. л.